Analisis Rencana Pelaksanaan Pembelajaran (RPP) dengan Praksiologi - Benny Wahyudi (Jurnal Indonesia Sosial Teknologi, 2022)
Learning Implementation Plan (RPP) is a plan that describes the procedures and management of learning to achieve one or more basic competencies that have been described in the syllabus. Praxeology is a purposeful framework for understanding human behavior. It gives the law of universal action. Praxeology consists of four components, namely the type of assignment, technique, technology, and theory. This content analysis or content is usually available in qualitative analysis. The content analyzed was in the form of a lesson. The assignment type component includes on task behavior and off task behavior. The technical component is appropriate because the information at each meeting has continuity. The technology component in the learning media has not met the praxeological component so it is necessary to increase the information and communication technology-based learning media. As well as adjustments to the use of technology that students already have. The theory component contains constructivist theory so that students can gain knowledge based on their own learning experiences.